2019
DOI: 10.3390/nano9091229
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Tetrachloroaurate(III) Ions With Bioligands: Role of the Thiol and Amine Functional Groups on the Structure and Optical Features of Gold Nanohybrid Systems

Abstract: In this review, the presentation of the synthetic routes of plasmonic gold nanoparticles (Au NPs), fluorescent gold nanoclusters (Au NCs), as well as self-assembled Au-containing thiolated coordination polymers (Au CPs) was highlighted. We exclusively emphasize the gold products that are synthesized by the spontaneous interaction of tetrachloroaurate(III) ions (AuCl4¯) with bioligands using amine and thiolate derivatives, including mainly amino acids. The dominant role of the nature of the applied reducing mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 126 publications
1
43
0
Order By: Relevance
“…The aim of this Special Issue on "Supramolecular Gold Chemistry" was to provide a unique international forum aimed at covering a broad description of results involving the supramolecular chemistry of gold with a special focus on the gold-sulfur interface leading to hybrid materials, ranging from gold-thiolate complexes, [3] to thiolate-protected gold nanoclusters [4][5][6][7][8][9][10][11] and gold-thiolate supramolecular assemblies or nanoparticles. [12][13][14] The role of thiolates on the structure and optical features of gold nanohybrid systems (ranging from plasmonic gold nanoparticles and fluorescent gold nanoclusters to self-assembled Au-containing thiolated coordination polymers) has been highlighted in the review article by Csapó and coworkers [14].…”
mentioning
confidence: 99%
“…The aim of this Special Issue on "Supramolecular Gold Chemistry" was to provide a unique international forum aimed at covering a broad description of results involving the supramolecular chemistry of gold with a special focus on the gold-sulfur interface leading to hybrid materials, ranging from gold-thiolate complexes, [3] to thiolate-protected gold nanoclusters [4][5][6][7][8][9][10][11] and gold-thiolate supramolecular assemblies or nanoparticles. [12][13][14] The role of thiolates on the structure and optical features of gold nanohybrid systems (ranging from plasmonic gold nanoparticles and fluorescent gold nanoclusters to self-assembled Au-containing thiolated coordination polymers) has been highlighted in the review article by Csapó and coworkers [14].…”
mentioning
confidence: 99%
“…There are many methods to prevent or limit the toxic effects of metallic nanoparticles and metal oxides. Studies have shown that changing the shape and size of particles, and methods to modify their surface, can lead to the formation of nanoparticles with the desired properties, but without a toxic effect [16]. Nanoparticles used as drug carriers are exposed to a physiological medium consisting of high levels of salt and various proteins.…”
Section: Methods For Reducing the Toxicity Of Drug Carriers Based On mentioning
confidence: 99%
“…Functional groups act both as stabilizers and reducers in synthesis of gold nanoparticles. The products obtained in this way were characterized by high stability and, what is significant, high biocompatibility [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials, exploited in a variety of strategies for targeted drug delivery, have significantly improved the efficacy of tumor therapy with less or none side effects on healthy tissues (Kanamala, Wilson, Yang, Palmer, & Wu, ; G. Liu et al, ; W. Wang et al, ; W. Zhang et al, ). Owing to their unique properties, gold nanoparticles (AuNPs) have been developed as multifunctional nanoplatforms and have been widely used in a variety of tumor therapies, including chemotherapy, gene therapy, photothermal therapy (PTT), and radiotherapy (RT; Ou, Zhou, Chen, & Tan, ; Sharifi et al, ; Ungor, Dekany, & Csapo, ). A wide range of synthetic methods have been developed to prepare AuNPs with controllable size and shape to adapt to different biological functions (Frens, ; Huang, Neretina, & El‐Sayed, ).…”
Section: Introductionmentioning
confidence: 99%